Posted by **jasmine20** on Sunday, March 25, 2007 at 11:20pm.

i am up to this point in my problem but i don't know what to do next with it can someone show me.

Directions: Simplify by combining like terms

x radical(18) minus 3radical(8x^2)

these are the steps that i've done so far.

= x radical (2*9) -3radical (2*4*x^2)

= x radical (2) * radical (9) - 3 radical (2) * radical (4) * radical (x^2)

=x * radical (2) * 3 - 3*radical (2) * 2 * x

from here i do not know can someone help me finish.

You are so close

=x*√2*3-3*√2*2*x

=3x√2-6x√2

=-3x√2 or -3√2*x